ECONOMIC ASSESSMENT OF AGRICULTURE DEVELOPMENT AND PROSPECTIVE DIRECTIONS OF AGRARIAN REFORMS IN THE REPUBLIC OF AZERBAIJAN - Ramina MUSTAFAYEVA; Yegana ABBASOVA; Ruhiyya QAMBAROVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper examines the stages of agricultural development strategies of the Republic of Azerbaijan. Taking into account that, our country is among the developing countries, agriculture is one of the leading sectors in the country after the oil industry. Agriculture plays an important role in the food security of the country and the socio-economic development of the regions. From this point of view, the state has always focused on the development of agriculture. Considering all the things mentioned above, the article has attempted to show the dynamics of development of agriculture in the economy of the country. Also, the article assessed the current state of agriculture in accordance with agrarian reforms carried out in the post-Soviet period and after the independence of the state. In the development of a competitive environment, the owner entities play large role. In the article found a place, development of enterprises in agriculture and their regulation by the state in accordance with the requirements of a market economy. Also, the dynamics of production, productivity and self-sufficiency of the main types of crop and livestock products were analyzed and evaluated on the basis of statistical data of the Azerbaijan Republic. It should be noted, the assessment also examined the impact of agrarian reforms on agricultural development after state independence. During the observation were used, methods of logical history, analysis-synthesis, induction- deduction. Finally, the conclusions and recommendations are based on the provisions obtained from the analysis.